OXIDATIVE-ANTIOXIDANT CHANGES OF LOW-DENSITY LIPOPROTEINS AND THEIR ASSOCIATION WITH ATHEROSCLEROTIC RISK FACTORS IN MALE NOVOSIBIRSK POPULATION - Yu. I. Ragino; A. S. Krivchun; M. V. Ivanova; L. V. Shcherbakova; S. K. Malyutina; Yu. P. Nikitin; M. I. Voevoda (Российский кардиологический журнал, 2012)
Aim. To investigate the parameters of oxidative-antioxidant changes of low-density lipoproteins (LDL) in a male population, and to study their association with selected risk factors of atherosclerosis and coronary heart disease (CHD). Material and methods. This population study included 1024 Novosibirsk men, aged 47–73 years. Questionnaire survey, standard cardiological examination, anthropometry, blood pressure (BP) measurement, and electrocardiography (ECG) were performed. Assessed biochemical parameters included total cholesterol (TCH), triglycerides (TG), high-density lipoprotein cholesterol (HDL–CH), high-sensitivity C‑reactive protein (hsCRP), glucose, baseline lipid peroxidation (LPO) and fat-soluble antioxidants (alpha-tocopherol, retinol, beta-carotene, xanthines) in LDL, LDL resistance to oxidation in vitro, and autoantibodies to oxidized LDL (oxLDL). Results. For the male Novosibirsk population, the region-specific 10% and 90% cutoff points for the percentile distribution of baseline LPO in LDL, LDL resistance to oxidation at initiation and propagation stages of oxidative LDL modifications, lipophylic LDL antioxidants, and autoantibodies to oxLDL are presented. Correlations were observed between baseline LPO in LDL and hsCRP levels; between LDL resistance to oxidation and blood lipid profile, body mass index (BMI), and CHD; between the levels of autoantibodies to oxLDL and hsCRP or BMI; between LDL antioxidants (particularly alpha-tocopherol) and blood lipid profile, hsCRP, BMI, and CHD. In men, increased levels of LPO in LDL, reduced levels of LDL antioxidants, and decreased LDL resistance to oxidation were independently associated with elevated blood levels of TCH, TG, and hsCRP, low HDL–CH levels, increased BMI, and present CHD. Conclusion. In the examined male population, regional reference values for the parameters of oxidative-antioxidant LDL changes were identified. They were independently associated not only with present CHD, but also with pathogenetically significant, potentially atherogenic coronary risk factors.